Association between muscle strength and dementia in middle-aged and older adults: a nationwide longitudinal study - Jin, Wei; Liu, Sheng; Huang, Li; Xiong, Xi; Chen, Huajian; Liang, Zhenzhen (Journal of psychiatric research, 2025)
Background - As the population aging of the world, the number of people with dementia is increasing. The aim of this study was to investigate the potential impact of muscle strength on the risk of dementia among middle-aged and older adults in the UK. - Methods - This study used data from 5916 participants aged 50 years and over from the English Longitudinal Study of Ageing (ELSA) with a median follow-up of 9.2 years. Muscle strength was assessed by handgrip strength (HGS), standardized HGS (BMI- or weight-standardized), and chair-rising time, with participants categorized into tertiles by gender based on these measures. Cox Proportional Hazards Model was used to assess the association between muscle strength and risk of dementia. - Results - A total of 197 participants (3.33 %) developed dementia during follow-up. Regarding HGS, participants with low HGS had a higher risk of dementia (HR = 2.84, 95 % CI: 1.64-4.91). In analyses of standardized grip strength, participants with low muscle strength were also associated with a higher risk of dementia: BMI-standardized grip strength (HR = 2.20, 95 % CI: 1.35-3.58) and weight-standardized grip strength (HR = 1.74, 95 % CI: 1.11-2.74). In addition, those who spent more time standing had a higher risk of dementia than those who spent less (HR = 2.75, 95 % CI: 1.71-441) in an analysis of Chair rising time, which represents lower limb muscle strength. Subgroup analyses showed that these associations remained stable across age [in the middle-aged (50-64 years) and elderly (≥65 years) groups] and sex groups. The results of sensitivity analyses after excluding participants diagnosed with dementia within 2 years of baseline remained consistent with the main analysis. - Conclusions - In conclusion, this study demonstrated that muscle strength (including HGS, standardized HGS and Chair rising time) is strongly associated with the development of dementia. Thus, muscle strength (including upper and lower extremity strength) plays a key role in preventing and delaying dementia, highlighting the importance of extremity muscle strength in dementia risk assessment. These findings provide new perspectives for the development of muscle strength intervention strategies in middle-aged and older populations and provide a scientific basis for the early detection and prevention of dementia.
Gesehen am 28.01.2026